Assessment of Anti-Hepatitis B Virus Activity of Leaf Extract of Morinda Citrifolia - Umaru, Isaac John; Yuguda, Ismail Yunusa; Ngbede, Ocheifa Mathew; Iseko, Kingsley Iyoko; Abdulrasheed, Lubabatu; Akafa, Tensaba Andes; Okwori, Ameh Godwin (Darul Yasin Al Sys, 2025)
Hepatitis B virus infection remains a global health problem, it is a leading cause of liver disease and a possible worldwide source of severe morbidity and mortality. The current standard therapy using interferons or antiviral agents is not successful in all cases and is associated with severe side effects. Consequently, the development of new medicines for the treatment of HBV is still relevant. This experimental study was therefore performed to assess the anti-hepatitis B virus (HBV) potential of Leaf extract of Morinda citrifolia. The methanolic extracts of the Leaf extract of Morinda citrifolia first assessed for cytotoxicity on HepG2.2.15 cells and cytotoxicity concentration (CC50) values were resolved. The methanolic extracts of the Leaf extract of Morinda citrifolia was additionally examined on HepG2.2.15 cells for anti-HBV potential by examining the inhibition of HBsAg and HBeAg production in the culture supernatants, and calculating their half-maximum inhibitory concentration (IC50) and therapeutic index (TI) values. Out of four concentration only three exhibit inhibition of HBsAg production in an increasing dose and time dependent manner. These four concentrations are 100 μg/mL, 200 μg/mL, 300 μg/mL and 400 μg/mL, with IC50 values of 21.15, 24.51, 118.94, 17.65, 20.93 μg/mL, respectively. Moreover, the presence of terpenoids, tannins, alkaloids and flavonoids that could contribute to antiviral efficacy was validated with a qualitative phytochemical study of active extracts.